An Analysis of Moral Values in The Zootopia Movie - Masyitah; Eusabinus Bunau; Eka Fajar Rahmani; Rahayu Apriliaswati; Eni Rosnija (Kirana Publisher (KNPub), 2023)
This research aimed to identify the types of moral values ​​and describe how these moral values ​​are presented in the Zootopia movie, directed by Byron Howard and Rich Moore. The research design was a qualitative descriptive study; the data sources are the movie itself and the movie script of Zootopia. The SPEAKING Model (setting and scene, participants, ends, act sequence, key, instrumentalities, norms, and genre) by Dell Hymes is used as a framework for assess the conversation in the movie. The research results showed that this movie contained twelve utterances classified based on the types of moral values defined by Josephson and Hanson, such as trustworthiness, respect, responsibility, fairness, caring, and citizenship. Also, the morals are analyzed more profoundly using the SPEAKING Model by Dell Hymes. The moral values ​​described in this study have important implications for teachers and other researchers, which can encourage the use of tools in analyzing literary works and can be applied in life.